Psycho-social Factors that Lead to Heroin Addiction among Young Males in Turkey - Alptekin, Kamil; Mutlu, Ercan; Paltun, Salih Cihat; Göka, Erol (Addicta: The Turkish Journal on Addictions, 2018)
Heroin has become a subject of growing concern in Turkey due to the rapid increase among young adults using and becoming addicted to it. Thus, the purpose of this qualitative study is to identify the psycho-social factors that lead to heroin addiction in young males based on their life experiences. The sample consists of 18 young males (aged 18-24) who have been diagnosed with heroin addiction and are currently receiving inpatient treatment for substance use disorder. Based on the semi-structured face-to-face interviews, the findings reveal that heroin addiction develops gradually over time as an outcome of various preliminary factors. Such factors include: lack of interest in school and family relationships, growing up in the street culture, a tendency toward addiction, and negative role models/peers. Moreover, the progression of addiction results in physical, mental, social, and economic losses, all of which trigger the desire to quit heroin and seek treatment. The implication of the findings is that, because heroin addiction is an outcome of various factors, multi-dimensional and multi-disciplinary studies on heroin addiction that include the life experiences of heroin addicts are necessary.To
Keywords: Heroin; Heroin addiction; Young male heroin addicts; Street culture; Qualitative research